The characteristics and genetic mechanisms of the Upper Permian Shangwuerhe clastic reservoir in the eastern Junggar Basin, Northwest China - Qin, Zhijun; Tang, Yong; Chang, Qiusheng; Liu, Chaowei; Ren, Haijiao (Frontiers in Earth Science, 2023)
In this paper, the lithology, pore type, throat structure, and physical characteristics of the sandstone and conglomerate reservoirs of the Upper Permian Shangwuerhe Formation in the Fukang Sag of the Junggar Basin were analyzed through rock cast thin section, scanning electron microscopy, fluid inclusions, piezometric mercury, and porosity–permeability analysis. In addition, the reservoir densification mechanism and the genesis of deep effective reservoirs were discussed. The results show that the reservoir is dominated by lithic sandstone (or lithic sandstone conglomerate). The lithic fragments primarily comprise tuffaceous volcanic rocks, supported by grains and cemented by clay, carbonate, authigenic quartz, and laumontite. The reservoir properties are characterized by extra-low porosity and permeability, and the pore type is dominated by inter- and intragrain dissolved pores of lithic fragments, feldspar, and quartz. The pore connectivity is poor due to poorly sorted extra-fine throat channels. The tightness of the reservoir.is due to the strong cementation of calcite, chlorite, montmorillonite, illite-montmorillonite mixed layer, authigenic quartz, and laumontite. Furthermore, the large amount of Ca2+ released by the hydration of tuff rock debris and intermediate–basic volcanic rock debris and the CO2-rich thermal fluid from the deep layers cause the development of several calcites. The formation of several montmorillonites is mainly related to the alteration of filled volcanic ash, and the hydration of volcanic tuff material primarily causes the development of laumontite cementation. The dissolution of feldspar and various volcanic lithic fragments by acidic fluids triggers the physical improvement of the reservoir in the local section.